Assessing the Diagnostic Accuracy and Health System Impact of Optical Technologies in Medical Laboratories: Implications for Public Health Policy and Healthcare Efficiency (The Review of Diabetic Studies, 2025)
Background: The range of optical technologies, which include flow cytometry, spectrophotometry, digital microscopy, OCT, and Raman spectroscopy, has had a dramatic impact on the current laboratory diagnostics. However, no thorough evaluation of the accuracy measures used by these devices and the impact that they have on healthcare and public health policy can be found in the literature.Objectives: In this paper, we attempt to (1) assess the diagnostic accuracy of leading laboratory optical technologies, (2) measure the impact of these tools on the operational efficiency of laboratories, including their turnaround times (TAT) and cost-effectiveness, and (3) generate public health recommendations regarding the implementation and use of laboratory technologies.Methods: The mixed research methodology approach was chosen for this study, which involves conducting a systematic literature review of relevant peer-reviewed studies written between 2020 and 2024 and a retrospective cross-sectional analysis of laboratory data from 14 accredited laboratories at primary, secondary, and tertiary levels of care in four countries. The diagnostic accuracy indices, including sensitivity, specificity, PPV, NPV, and AUC were identified.Results: Optical devices showed consistent performance with respect to their diagnostic sensitivity and specificity: flow cytometry showed a pooled sensitivity of 96.7% and specificity of 97.3% for the immunophenotyping of hematological malignancies. Artificial intelligence-assisted digital microscopy had a sensitivity of 94.2% for the detection of malaria parasites. Raman spectroscopy showed an AUC value of 0.961 in tissue classification of cervical cancer. The introduction of optical devices was accompanied by an average reduction of TAT by 38.6% and 27.3% reduction in diagnostic errors. The cost per reportable test dropped by an average of 21.4% after the introduction of optical technologies.Conclusion: Optical technologies provide significant advantages in terms of diagnostics and efficiency for medical laboratories, which need to be incorporated into national laboratory systems through targeted public health policies.